THE CULTURAL VALUES OF TOBA BATAK IN BULU TURAK ORAL TRADITION SIMANINDO KAB.SAMOSIR - Widy R.M Sitorus and Sri Minda Murni (LINGUISTICA, 2017)
This study focused on finding out the cultural values of Toba Batak in Bulu Turak Oral Tradition in Simanindo, Kab.Samosir. The objectives of this study were to find out the cultural values of Toba Batak, to describe the realization of cultural values linguistically and to describe the reason of cultural values of Toba Batak  realization in bulu turak oral tradition. This research was conducted by using descriptive qualitative design.The data were 29 utterances of cultural values of Toba Batak that were taken from bulu turak transcription.The findings of this research were nine cultural values of Toba Batak was containing kinship 17%, religion 13%, extended family 20%, respect 10%, wealth 6%, modernization 3%, justice 3%, nurture 6%, and conflict 24%. The most dominant cultural values of Toba Batak is conflict 24%. The realization of cultural values of Toba Batak linguistically was described by the representation of experience was containing, mental process, verbal process, relational process, and the last finding was the reason of cultural values of Toba Batak realization because of sociocultural of character ancient, the character’s love, and believe to the character creature ( mula jadi nabolon ).